Beneficiation of phosphates technology advance and adoption - Zhang, Patrick (Society for Mining, Metallurgy, and Exploration, 2010)
Beneficiation of Phosphates: Technology Advance and Adoption is the exclusive source of information on research and technology advances in phosphate mineral processing. More than 100 internationally respected authors from 20 countries explore the latest developments in an industry experiencing unprecedented change and prosperity.
Keywords: Phosphates.; Ore-dressing.; Flotation.; elektronické knihy; electronic books